Thalassemia Phenotypes and Genotypes in Taiwan: A Retrospective Study Based on Thalassemia Screening of Young Men for Military Conscription. (June 2015) - Lee, Hsiao-Wei; Han, Shao-Min; Yang, Youngsen; Lin, Tseng-Hsi; Tzeng, Huey-En; Chang, Kuang-Hsi; Hwang, Wen-Li; Teng, Chieh-Lin J.
Abstract Prenatal thalassemia studies from Taiwan show that one-third of fetuses with genetic abnormalities have β-thalassemia major (β-TM). However, the phenotypes and genotypes of adult thalassemia warrant further investigation. From September 2006 to April 2014, 741 male candidates drafted for military service with mean corpuscular volume (MCV) <80 fL and serum ferritin >20 µg/L were analyzed. The results showed that the detection rates of α- and β-thalassemia (α- an β-thal) were 50.20% (372/741) and 49.12% (364/741), respectively. Only five patients (0.67%) were diagnosed with both α- and β-thal. The – –SEA/αα mutation was found in 76.88% (286/372) of α-thal patients. Heterozygous mutations in IVS-II-654 (C > T) and codons 41/42 (–TCTT) accounted for 55.77% (203/364) of β-thal cases. The leukocyte counts for α- and β-thal were 6241.74 ± 1552.99 and 6622.87 ± 1814.41 × 109/L, respectively (p = 0.007). The α-thal patients had lower red blood cell (RBC) mass (5.85 ± 0.44 × 1012/L vs. 6.09 ± 0.45 × 1012/L; p < 0.001) and higher hemoglobin (Hb) (12.82 ± 0.72 vs. 12.35 ± 0.71 g/dL; p < 0.001) than β-thal patients. Mean serum ferritin values were 169.67 and 241.36 µg/L, respectively, in α- and β-thal patients (p < 0.001), indicating more profound ineffective erythropoiesis in β-thal. Only four of the 741 patients underwent further hematological follow-up. Our study suggests that iron overload might be a potential problem in β-thal patients; therefore, regular follow-up is highly recommended.